INTEGRATION OF THE VALUES OF AMANAH, JUDICIAL, DELIBERATION, ITQAN, AND IHSAN IN THE LEADERSHIP PRACTICE OF ABCD-BASED MADRASAH HEADS - Mulyawan Safwandy Nugraha; A. Heris Hermawan; Ai Rohayani (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
In the face of contemporary challenges in madrasah leadership, strengthening Islamic values is essential to foster ethical, effective, and community-oriented leadership practices. This study aims to explore how the values of amanah (trustworthiness), adil (justice), musyawarah (deliberation), itqan (excellence), and ihsan (benevolence) are integrated into school leadership practices through the Asset-Based Community Development (ABCD) approach, and how this integration impacts program outcomes and managerial routines. Employing a qualitative case study design, data were gathered through in-depth interviews, participatory observation, and document analysis involving 10 school principals across Bandung City. The findings reveal that Islamic values were successfully internalized across all ABCD stages, positively influencing asset mapping quality, action plan feasibility, and stakeholder satisfaction. The study concludes that integrating Islamic values not only strengthens the spiritual dimension of leadership but also creates a participatory and exemplary educational management model. These results imply the urgency of developing structured and contextual Islamic leadership training as a response to the evolving demands for professional and value-based school leadership